A Priority-based Dynamic Link Scheduling Algorithm Using Multi-criteria Decision Making in Wireless Body Area Networks - Kim, Beom-Su; Kim, Ki-Il (Proceedings - International Symposium on Modeling, Analysis, and Simulation of Computer and Telecommunication Systems, 2020)
IEEE 802.15.6, which is the standard for wireless body area networks (WBANs), defines a unique link allocation interval called the managed access phase to meet the QoS requirements of medical applications. The hub grants an uplink allocation interval to the node according to predetermined scheduling policies; however, the IEEE 802.15.6 standard does not consider user priorities in the uplink scheduling. To address this problem, many priority-based link scheduling algorithms have been proposed; however, these algorithms ignore the unique characteristics of WBANs, such as changes in body posture and damage to body tissue, thereby leading to a waste of resources. To overcome these limitations, in this study, we propose three scheduling parameters that are suitable for WBANs, and logically determine the relationship between the proposed parameters using the multi-criteria decision making (MCDM) method. Furthermore, a priority-based dynamic link scheduling algorithm is proposed, which is based on the results of the MCDM. The simulation results prove that our proposed approach can balance the resource allocation, while maintaining the performance of high-priority nodes in terms of throughput, delay, and power consumption.